THE INVESTIGATION OF THE ELASTIC ANYSOTROPHIE FOR SOLVING THE PROBLEMS OF THE TECHTONOFACING ANALYSIS - BEZRODNYI, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The new acoustic method of the textural analysis of polymineral breeds on the basis of research of a structure of samples Krivorozhya is described.